GASTRONOMIC TOURISM SCENARIO OF AN INTERNATIONAL DESTINATION BASES ON NETNOGRAPHY MODEL - Lacruhy Enríquez, Claudia Carolina (2024)
The objective of the research was to design a netnography model for the analysis of the gastronomic tourism scenario of the international destination of Los Cabos, Mexico through tourism promotion and digital footprint reviews. The research was qualitative, exploratory and descriptive in scope. A netnography model was designed, in two stages, first a guide for the corporate website for the Los Cabos Tourism Trust, in the tab of restaurants by region (gastronomic offer) and second category a virtual observation guide for evaluation and review of comments on TripAdvisor (evaluation of diners). The results showed that in the culinary scene of the international destination of Los Cabos diners have diverse categories representative of the municipality, mainly: seafood (42%), international cuisine (40%), Mexican cuisine (31%), luxury restaurants (19%) and signature cuisine (12%). The garden-to-table experience based on sustainable gastronomy is a trend among diners. There are three gastronomic proposals in the rural zone of the municipality of Los Cabos with regional food, in addition to a gastronomic district 23400, composed of 15 restaurants. In relation to the perception of the diners in the evaluations on TripAdvisor is 4.5/5 so it was considered positive, they indicated high satisfaction in quality, service, atmosphere and ambience.  The profile of the traveler who opts for gourmet food rates it as 5/5 excellent. In conclusion, the proposed model facilitated the identification of components of the gastronomic scenario of the tourist destination.